O direito à cidade e a cultura marginal : a narratividade como luta por visibilidade - Vieira, Anna Paula Ferraz Dias (2018)
The divided city territorializes inequalities and fragments its spaces, legitimized by a hegemonic discourse that serves the dominant ideas and values. From its physically and socially fragmented spaces it chooses those to illuminate, to show as the image